Implications of attention deficit and hyperactivity disorders on neurocognitive performance and recovery in collegiate student–athletes. Issue 11 (25th May 2017) - Ketcham, Caroline; Patel, Kirtida; Hall, Eric
Abstract : Background: Approximately 3–13% of college-aged students have a diagnosis of Attention Deficit/Hyperactivity Disorder (ADD/ADHD) which is characterised by impulsivity, inattention, and cognitive speed deficits which affects academic, athletic, and occupational performance even when treated. Objective: The purpose of this study was to examine baseline neurocognitive differences in collegiate student-athletes with diagnosis of ADD/ADHD as well as recovery time from concussion. Design: Cross-sectional. Setting: Collegiate campus in North Carolina Participants: Participants of this study included 1161 student-athletes (varsity, n=272 and club, n=889). 89 participants were followed post-concussion with 8 having diagnosis of ADD/ADHD. Assessment of risk factors: Diagnosis of ADD/ADHD and days of recovery following concussion. Outcome measures: Participants completed the Immediate Post-Concussion Assessment and Cognitive Testing which generated composite scores on Verbal Memory, Visual Memory, Visuomotor Speed, and Reaction Time as well as Total Symptom Scores. Main results: There were no significant differences between groups for Visual Memory, Reaction Time and Total Symptom Scores (p>0.05). Those with diagnosis of ADD/ADHD (n=146) had lower verbal memory(mno =85.3, %95 CI: [84.6, 86] vs. madd =82.5, %95 CI:[80.7, 84.3], F(1, 1145)=8.6, p=0.003) and slower visuomotor speed (mno=41.7, %95 CI: [41.3, 42.7] vs. madd=40.5, %95: CI:[39.5, 41.5], F(1, 1145) =8.6, p=0.027) compared to those without a diagnosis. Those with ADD/ADHD took almost two times longer to recover than those without (mno =7.3 days, %95 CI: [6.2, 8.4] vs. madd =13.3 days, %95 CI:[9.4, 17.2], F(1, 89) =9.8, p=0.002). Conclusions: Student-athletes with diagnosis of ADD/ADHD may benefit from targeted interventions as part of return to play/learn protocols. Previous research has shown that practice may help rehabilitate those with cognitive and visuomotor processing speed deficits following a concussion. Competing interests: None.